2017
DOI: 10.18869/mjiri.31.17
|View full text |Cite
|
Sign up to set email alerts
|

Integrating behavioral and social sciences components into a competency-based MD program curriculum: A qualitative study on opinions of faculty members

Abstract: Background: Behavioral, social, psychological and biological factors influence health and disease; and, to achieve professional competency, physicians should be knowledgeable about their society and its inhabitants’ behavior. This knowledge will help physicians to become competent in communication, professional behavior, self-awareness, ethical reasoning, and understanding cultural and social differences. In this regard, this research is an attempt to explore perspectives of medical faculty members on necessit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In a content analysis study, in which medical faculty members’ perspectives on the necessity of incorporating BSS into the medical curriculum were explored, six themes were emerged. The results of this study showed that integrating BSS into medical curriculum leads to facilitating health behavior changes [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a content analysis study, in which medical faculty members’ perspectives on the necessity of incorporating BSS into the medical curriculum were explored, six themes were emerged. The results of this study showed that integrating BSS into medical curriculum leads to facilitating health behavior changes [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although the Liaison Committee on Medical Education (LCME) and other accreditation bodies in the world have emphasized the need to consider BSS in accreditation of medical schools, incorporation of BSS in the medical curriculum has been variable at many schools around the world [ 12 ] and social medicine is taught at less than 10 % of medical schools that are accredited by the LCME [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The professor's role is of utmost importance in inculcating students with humanism in clinical education. Thus, the academia must plan for the selection of clinical professors and invest in the enhancement of humanistic behaviors in clinical education so that humanism would restore its status in medicine by empowering the professors [37].…”
Section: Discussionmentioning
confidence: 99%
“…Humanitarian values in clinical settings are mostly transferred to students through role modeling position of professors and the hidden curriculum [ 10 , 35 – 37 ]. It is expected that human virtues, including humanitarianism, compassion, and empathy, be explicitly enhanced while offering medical care [ 38 ].…”
Section: Discussionmentioning
confidence: 99%